Pre-Service Biology Teacher : An Analysis of The Learning Style and Interest - Sadikin, Ali; Rusdi, Muhammad; Hasibuan, Muhammad Haris Effendi; Siburian, Jodion (Asian Journal of Science Education, 2024)
The purpose of this study was to determine the learning style and interest of prospective biology teacher students who will take microteaching lectures. The research method used descriptive quantitative. Samples were obtained through purposive sampling. Data were collected using questionnaires and analyzed descriptively (collection, reduction, and conclusion). The results showed that the most dominant learning style was visual learning style. Meanwhile, the most dominant learning interest among prospective biology teacher students at Jambi University is related to music. Therefore, the recommendation from this study is to organize microteaching with visual and music-based media.